Gambaran Pengetahuan Ibu Tentang Stunting Di Desa Lebih Kabupaten Gianyar Tahun 2020 - Kadek Sri Ariyanti; Ni Made Indra Peratiwi (STIKES ADVAITA MEDIKA TABANAN, 2021)
Stunting is a chronic nutritional problem experienced by the State of Indonesia that must be addressed. Stunting is a condition of failure to thrive in children under five due to chronic malnutrition so that the child is too short for his age. The importance of conducting research on stunting in order to assist the government in carrying out work programs to reduce the incidence of stunting. The purpose of this study is to describe the knowledge of mothers about stunting in the village of Lebih, Gianyar Regency in 2020. The method of implementing this research is descriptive with a cross-sectional design. The sample in this study were 78 mothers of infants and were taken systematically. This research was conducted in Desa Lebih, Gianyar Regency in August 2020. Data processing used univariate analysis. The results showed that most respondents had good knowledge about stunting, as many as 65 people (83.3%). So the conclusion in this study is that the description of maternal knowledge about stunting in the village of Lebih, Gianyar Regency, is mostly in the good category. It can be investigated the factors that influence the occurrence of stunting.